Morphology-independent stable white-light emission from self-assembled two-dimensional perovskites driven by strong exciton–phonon coupling to the organic framework - Thirumal, Krishnamoorthy (2020)
Hybrid two-dimensional (2D) lead halide perovskites have been employed in optoelectronic applications, including white-light emission for light-emitting diodes (LEDs). However, until now, there have been limited reports about white-light-emitting lead halide perovskites with experimental insights into the mechanism of the broadband emission. Here, we present white-light emission from a 2D hybrid lead chloride perovskite, using the widely known phenethylammonium cation. The single-crystal X-ray structural data, time-resolved photophysical measurements, and density functional theory calculations are consistent with broadband emission arising from strong exciton–phonon coupling with the organic lattice, which is independent of surface defects. The phenethylammonium lead chloride material exhibits a remarkably high color rendering index of 84, a CIE coordinate of (0.37,0.42), a CCT of 4426, and photostability, making it ideal for natural white LED applications.